Easy dairy-free ketogenic recipes : 200+ low-carb family favorites for weight loss and health - Emmerich, Maria (Victory Belt Publishing Inc., 2018)
Collects high-fat, low-carbohydrate recipes that are also dairy-free for those following the ketogenic lifestyle, including such options as spicy fried eggs with chorizo, coconut chicken, crab Louie salad, paella, and Cajun shrimp.